Design and experiment of impeller seed guide device for rice internal suction hole direct seeding device - Yansong Shang; Bo Zhou; Jitao Yang; Shun Zhang (Scientific Reports)
Abstract Multi-grain hole-forming sowing and uniform hole spacing are important agronomic requirements for precise hole-direct seeding of rice.This paper designs a kind of impeller type seed guiding device. The main structural parameters of the impeller seed guide device were analyzed by constructing the kinematics model of the rice seed in the impeller seed guide process. The experiment analysis were carried out with the long-grain rice variety Chuangliangyou 4418 as the seeding object. The optimal structural parameter combination of seeding-guiding device was determined as inner impeller radius 56 mm, blade offset angle 11° and seeding angle 36°. On this basis, the seeding performance test of different seed guiding devices of internal suction seed-metering device was carried out by using rice seeds with different external dimensions. The test results show that the impeller has better cavitation and hole spacing uniformity than the seed guide tube. The average hole diameter is not higher than 21.7 mm, the qualified rate of hole diameter is not lower than 96.1%, and the coefficient of variation of hole spacing is not higher than 10.1%. Compared with the seed guide tube, which is increased by 32%, 16% and 34% respectively, and the average hole distance is about 200 mm in theory.